Impact Angle Control Guidance Law With Seeker’s Field-of-View Constraint Based on Logarithm Barrier Lyapunov Function - Shou Zhou; Shifeng Zhang; Donghui Wang (IEEE Access, 2020)
In recent years, the strapdown system has become the significant trend of the development of precision guided weapons. In order to effectively hit the lightly armored targets, researchers have done a series of studies on the impact angle control. However, most of them ignored the field-of-view constraint of the strapdown seeker. The existing impact angle control guidance laws with the field-of-view constraint have obvious drawbacks to some extent. For example, most of them are only applicable against nonmaneuvering targets and some of them suffer sudden hopping of guidance command due to the use of switching logic. Taking the strapdown seeker missile as the research object, this paper studies the field-of-view constrained impact angle control guidance problem against stationary targets, constant speed targets and maneuvering targets. According to the sliding mode control theory, two kinds of sliding surfaces are designed to make the missile achieve high precision attack under a desired impact angle within the field-of-view constraint. A quadratic barrier Lyapunov function and a logarithm barrier Lyapunov function are used to guarantee that the sliding surfaces designed for the impact angle constraint and the field-of-view constraint can converge to zero in finite time respectively. Then, a nonlinear extended state observer is proposed to estimate the unmeasurable disturbance of the system and alleviate the undesirable chattering by compensating it with the estimation of the disturbance. Finally, the feasibility of the proposed law is verified by numerical simulations.